2020
DOI: 10.34179/revisem.v5i2.12219
|View full text |Cite
|
Sign up to set email alerts
|

Produção de conhecimento, experimentação-com-GeoGebra e visualização: possibilidades com o GeoGebra durante um curso de formação continuada

Abstract: O objetivo desse artigo é apresentar o desenvolvimento e análise de uma atividade matemática desenvolvida com o GeoGebra, por uma cursista que ensina Matemática, durante uma formação continuada realizada em Guaratinguetá/SP. Essa formação constituiu-se no cenário de investigação da pesquisa de doutoramento do primeiro autor. Ao término da atividade, passamos no computador da cursista, gravando a produção em um pen drive. Para analisar tal atividade, acessamos o protocolo de construção, do GeoGebra, buscando co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…The horizontal analysis of this section followed the classification of "focus of analysis" because we could investigate whether the objectives had been achieved and what the implications were. In the first group-using dynamic geometry software-we identified that research (Chinellato & Javaroni, 2020;Nogueira et al, 2020;Zambak & Tyminski, 2020) recognize the potential of dynamic geometry software for mathematics classes. The articles highlight that the interaction between the physical and digital environment benefits teachers' development.…”
Section: Results Conclusion and Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The horizontal analysis of this section followed the classification of "focus of analysis" because we could investigate whether the objectives had been achieved and what the implications were. In the first group-using dynamic geometry software-we identified that research (Chinellato & Javaroni, 2020;Nogueira et al, 2020;Zambak & Tyminski, 2020) recognize the potential of dynamic geometry software for mathematics classes. The articles highlight that the interaction between the physical and digital environment benefits teachers' development.…”
Section: Results Conclusion and Implicationsmentioning
confidence: 99%
“…To analyze the data production, we formulated a priori options that represented the main data production instruments used in research on teaching, education, and/or teacher education. The options were Anat et al (2020) x Bairral and Powell (2013) x Bulut and Isiksal (2019) x Chinellato and Javaroni (2020) x Filho and Gitirana (2022) x Kim and Park (2018) x Koh (2019) x Lin et al (2015) x Polly and Orrill (2012) x x x x Rocha (2016)…”
Section: Data Productionmentioning
confidence: 99%